اجتِهَادَاتُ ابنِ القَاسِمِ فِي التَّخْرِيجِ عَلَى أَقْوَالِ الإمَامِ مَالِك فِي المُدوَّنة الكُبْرَى - تامة, إلياس بن صالح (جامعة الشهيد حمه لخضر University of El-oued, 2023)
الملخص: تهدف هذه الرسالة إلى بيان مكانة التخريج في النظر الأصولي وأنه يعتبر من أهم الآليات والوسائل التي يمكن من خلالها التوصل إلى إدراك أصول الأئمة المجتهدين، واستثمارها في معرفة الأحكام الشرعية لما يستجد للناس من القضايا والاشكالات المختلفة، وتظهر كذلك أهمية التخريج في أنه يعتبر أداة تربط بين الحاضر والماضي، وبين التقليد والاجتهاد، وبين الجمود والمرونة، فهو آلية اجتهادية متجددة، وإنّ من أبرز من اشتهر بذلك في المذهب المالكي ابن القاسم، والذي لازم الإمام مالك مدّة طويلة، روى عنه جميع ما سمعه منه في مجالسه من فتاوى وضوابط وتعليلات، ولم يكتف ابن القاسم في المدوَّنة بالنّقل والرّواية فقط، بل اجتهد وذكر آراءه أيضا، ووافق الإمام مالكا في مسائل وخالفه في أخرى. وقد جاءت هذه الرسالة في فصلين؛ فالأول منها خصصته للجانب النظري للموضوع والتي يتعلق بالتعريف بابن القاسم والمدونة والاجتهاد والتخريج وبعض ما يتعلق بها من المباحث، وأما الفصل الثاني فقد كان خاصا بالدراسة التطبيقية وهي محصورة من كتاب الحدود إلى كتاب الدّيات، وقد ظهر بأن ابن القاسم استحق منزلة الْمخرِّج باقتدار وهو أولى بها من غيره من علماء المذهب المالكي، وقد تنقّل في اجتهاداته بين أنواع التخريج المختلفة، وقد تجلّى ذلك في القواعد والأصول الكثيرة التي خرّج عليها في المدونة. Abstract: The aim of this thesis is to highlight the significance of Takhreej (derivation of legal rulings) in the Usul Al-Fiqh (principles of Islamic Jurisprudence) and to show that it is one of the most important means through which the Usul of the Mujtahid Imams can be understood and utilized to derive Islamic legal rulings on various contemporary issues and problems. Furthermore, this thesis emphasizes the importance of Takhreej as a mechanism that links the past to the present, tradition to ijtihad, rigidity to flexibility, and as a constantly renewable method of ijtihad. One of the most prominent figures who excelled in Takhreej in the Maliki school of thought was Ibn Al-Qassim, who spent a long time studying under Imam Malik and who narrated all of the Imam's opinions, fatwas, regulations, and justifications that he heard in his gatherings. Ibn Al-Qassim did not just rely on narration and transmission in his work, but as well put forward his own opinions and agreed with Imam Malik on some issues and disagreed on others. The thesis is divided into two chapters, with the first chapter dedicated to the theoretical aspect of the subject, which includes the definition of Ibn Al-Qassim, Al-Mudawwanah, ijtihad, Takhreej, and related discussions. The second chapter focuses on the practical study, which is limited to the sections of Al-Mudawwanah from Al-Hudud to Ad-Dayat. It was found that Ibn Al-Qassim deservedly holds the status of being an outstanding Mukharrij (deriver) and is more deserving of this status than any other scholar of the Maliki school. His Takhreej methodology was varied and diverse, as evidenced by the many rules and principles that he derived in Al-Mudawwanah.”
- مِنْ كِتَابِ الحُدُودِ إِلَى كِتَابِ الدِّيَاتِ- دِرَاسَةٌ نَظَرِيَّةٌ تَطْبِيقِيَّةٌ
أطروحة دكتوراه تخصص فقه الاسرة في العلوم الإسلامية
Keywords: اجتِهَادَاتُ -ابنِ القَاسِمِ- التَّخْرِيجِ - المُدوَّنة الكُبْرَى; Jurisprudence - Ibn Al-Qasim - Graduation - The Great Code